Influencing Factors and Paths of the Coupling Relationship Between Ecosystem Services Supply–Demand and Human Well-Being in the Hexi Regions, Northwest China - Li, Yongge; Liu, Wei; Zhu, Meng; Feng, Qi; Yang, Linshan; Zhang, Jutao; Yin, Zhenliang; Yin, Xinwei (Remote sensing (Basel, Switzerland), 2025)
The coupling coordination relationship between ecosystem services supply–demand and human well-being in arid inland regions is increasingly vulnerable to imbalance risks under the combined pressures of climate change and intensified anthropogenic activities. Here, we assessed dynamic changes in ecosystem services supply–demand, human well-being, their coupling relationships and influencing factors in the Hexi Regions by integrating remote sensing data, ecological model, ecosystem services supply–demand ratio (ESDR), coupling coordination degree (CCD) model, and the partial least squares structural equation modeling (PLS-SEM). Our results showed that the six key ecosystem services supply, demand, and ESDR in the Hexi Regions from 1990 to 2020 exhibited greater ecosystem services surplus in the Qilian Mountains and stronger deficits in urban and surrounding areas of the Hexi Corridor. The deficit of water yield accounted for 32% in the Hexi Corridor with large cropland irrigated, four times that of the Qilian Mountains, indicating a serious supply–demand mismatch in space and time. Additionally, survival-oriented human well-being across regions is still dominant. Overall, the coupling relationship between ESDR and human well-being in the Hexi Regions progressed towards a high level of coordination, with higher values observed in the oases of the Hexi Corridor and the central and eastern Qilian Mountains. The ESDR of food production and water yield showed a higher coupling coordination level with human well-being in the Qilian Mountains, where the CCD was generally exceeded by 0.7. Climate, vegetation, and land use intensity were key drivers of spatial heterogeneity in CCD. Human well-being made a greater contribution to CCD than other elements in the influence paths. Our results can provide a reference for promoting coordinated development of the ecological environment and sustainable human well-being in arid inland regions.